Malaysia’s Tourism Industry Challenges amid the Covid-19 Pandemic - Liu Zi Yuan, Gareth (AEI Insights, 2023)
Although 2020 was supposed to be another “Visit Malaysia Year” and the Malaysian government had fully prepared for it; the Covid-19 pandemic put all the nation’s hopes on hold. The understanding of how the tourism industry in Malaysia can recover from a crisis is not yet complete, which has resulted in a lack of guidance for both industry professionals and researchers. The aim of this study is to determine the current state of Malaysia’s tourism industry, evaluate the challenges faced by the industry, and provide recommendations to facilitate its recovery. Adopting a systematic review method, the study examined the difficulties faced by the Malaysian tourism industry, the challenges in different sectors, and the government policies recorded in 40 identified reports. A framework of recommendation that synthesises relevant research and targets to cushion the industry’s recession was established in order to enlighten future research in a Covid-19 or post-Covid-19 society on Malaysia’s tourism industry.